“Kajian Bibliometrik Windcatcher untuk Ventilasi Alami dan Efisiensi Energi" - Suyento Tjuatja; Andi Prasetiyo Wibowo (Jurnal Arsitektur ARCADE, 2025)
Abstract: The windcatcher, as a traditional architectural element, is significant for natural ventilation and building energy efficiency in sustainable design. This study aims to map the global research landscape of windcatchers (2015-2025) and their applications in natural ventilation, energy efficiency, and building performance. Using a bibliometric analysis approach on 172 filtered and cleansed Scopus articles, VOSviewer and Scopus analytics were employed to identify trends, sources, geographical distribution, subject areas, and conceptual structure through keyword co-occurrence. The results indicate a dynamic and sustained research interest (peaking in 2017), multidisciplinary in nature (dominated by Engineering & Energy), with major contributors from the UK, Iran, US, and Egypt. Four main thematic clusters were identified: core focus on windcatcher-ventilation-CFD, thermal comfort-sustainability, experimental methodology, and fluid dynamics. These findings highlight the central role of digital tools like CFD and simulation for design optimization, provide a research roadmap, and identify innovation opportunities in Digital Architecture for energy saving. Keywords: Windcatcher, Bibliometric Analysis, Energy Efficiency Abstrak: Windcatcher, sebagai elemen arsitektur tradisional, signifikan untuk ventilasi alami dan efisiensi energi bangunan dalam desain berkelanjutan. Penelitian ini bertujuan memetakan lanskap riset global windcatcher (2015-2025) dan aplikasinya pada ventilasi alami, efisiensi energi, serta kinerja bangunan. Dengan pendekatan analisis bibliometrik terhadap 172 artikel Scopus yang telah disaring dan dibersihkan, VOSviewer dan analitik Scopus digunakan untuk mengidentifikasi tren, sumber, distribusi geografis, bidang ilmu, dan struktur konseptual melalui ko-okurensi kata kunci. Hasil menunjukkan minat riset dinamis dan berkelanjutan (puncak 2017), bersifat multidisiplin (dominan Teknik & Energi), dengan kontributor utama dari UK, Iran, US, dan Mesir. Empat klaster tema utama teridentifikasi: fokus inti windcatcher-ventilasi-CFD, kenyamanan termal-keberlanjutan, metodologi eksperimental, dan dinamika fluida. Temuan ini menyoroti peran sentral alat digital seperti CFD dan simulasi untuk optimasi desain, menyediakan peta jalan riset, dan mengidentifikasi peluang inovasi di Arsitektur Digital untuk penghematan energi. Kata Kunci: Windcatcher, Analisis Bibliometrik, Efisiensi Energi